2012
DOI: 10.5586/aa.2010.010
|View full text |Cite
|
Sign up to set email alerts
|

Direct and apparent residual effects of prohexadione - calcium applied to young cropping sweet cherry trees

Abstract: The same young cropping 'Regina' sweet cherry trees were foliar treated with prohexadione-calcium (Pro- Ca) in two consecutive years at a concentration of [ 125, 125 x 2, 250 ]-(A) and [ 250, 375, 500 ]-(B) mg ProCa l-1, respectively. The following year some trees from A-treatments were left untreated to observe carry-over effects (C). None of A-treatments influenced tree trunk, shoot extension and internode growth, whereas B-treatments reduced shoot extension and internode length, simultaneously in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…This study indicates that under Southern Ontario climatic conditions, P-Ca can markedly decrease the vegetative shoot growth of sweet cherry trees on rootstocks that promote medium-high to high vigor. This is consistent with the results of past experiments conducted in Summerland, BC (Guak et al 2005), Poland (Jacyna and Lipa 2010;Jacyna et al 2012), Chile (Cares et al 2014), and the Pacific Northwest region of the USA (Elfving et al 2003(Elfving et al , 2004(Elfving et al , 2005.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This study indicates that under Southern Ontario climatic conditions, P-Ca can markedly decrease the vegetative shoot growth of sweet cherry trees on rootstocks that promote medium-high to high vigor. This is consistent with the results of past experiments conducted in Summerland, BC (Guak et al 2005), Poland (Jacyna and Lipa 2010;Jacyna et al 2012), Chile (Cares et al 2014), and the Pacific Northwest region of the USA (Elfving et al 2003(Elfving et al , 2004(Elfving et al , 2005.…”
Section: Discussionsupporting
confidence: 92%
“…Limiting vegetative growth of extension shoots using combination sprays of P-Ca and ETH or P-Ca alone, which resulted in a 20%-50% reduction in shoot length, is unlikely to interfere with the desired balance of vegetative and fruiting required during the transition years. Prohexidione-calcium reduces shoot internode length without affecting the number of leaves per shoot (Jacyna and Lipa 2010;Evans et al 1997), and therefore it is unlikely to negatively influence the leaf area to fruit ratio, which markedly influences fruit size (Proebsting 1990). In experiment 2 in which growth of the primary (central) leader was inhibited greater than the extension shoots (by as much as ∼80%), selective spraying of the extension shoots only while avoiding treatment of the primary leader would be preferable during the establishment phase until the tree has reached its desired height.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results have been confirmed by Basak [8] in Jonagold apple trees and Miller [9] in Red Chief Delicious apple trees. Jacyna and Lipa [10] also found that application of prohexadione-calcium resulted in reduction of internode length, total growth per branch unit and shoot extension growth in apple and sweet cherry trees. Our results confirmed that the effect of paclobutrazol was stronger than prohexadione calcium on apple cultivars Fuji Zehn Aztec and Red Braeburn under high density planting system.…”
Section: Discussionmentioning
confidence: 92%
“…The higher fruit mean weight by 18-44 percent in apple cultivars Empire and Royal Court was noticed by prohexadione spray (Cline et al, 2007). In a study, Jacyna and Lipa (2011) reported that fruit diameter was reduced by 125 mg/l pro-ca (A-trees), but fruit shape (L/D ratio) and mass were reduced by 250 mg/l pro-ca (B-trees), and such reduction was also exhibited by C-trees treated with 250 mg/ l prohexadione-calcium. Prohexadione-calcium at 1.0 percent and 1.5 percent significantly increased mean fruit weight compared to untreated plants in Hass avocado plants (Mandemaker et al, 2005).…”
Section: Phenotypic Fruit Characteristicsmentioning
confidence: 90%